Minimal disease activity and associated factors in patients with psoriatic arthritis: cross-sectional study from a single center - Murat Bektas; Berk Çelik; Burak İnce; Yasemin Yalçınkaya; Bahar Artım Esen; Ahmet Gül; Murat İnanç (Rheumatology)
Introduction Psoriatic arthritis (PsA) is a heterogeneous disease with various manifestations such as dactylitis, enthesitis, spondylitis, and skin involvement. Minimal disease activity (MDA) has been successfully used in daily clinical practice and is considered a reasonable treatment target in patients with PsA. In this study, we aimed to evaluate the MDA status and associated factors in patients with PsA in our tertiary referral clinic.